2015
DOI: 10.1007/s00701-015-2625-z
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative predictive factors for surgical and functional outcomes in chronic subdural hematoma

Abstract: Clinicians should be more aware of general conditions and medical problems, especially in elderly patients. Membranectomy should be considered in patients with a long duration of symptoms or hypo-dense hematomas to promote good brain expansion and good mRS scores.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 27 publications
3
35
0
Order By: Relevance
“…Previous studies reported that age was associated with poor brain expansion and recurrence of CSDH. 9,11,21,26,29,30 Ro et al reported findings similar to ours, 29 showing that there were more recurrences of CSDH in patients with no brain expansion or brain underexpansion after surgery for CSDH, and that this was associated with age and the duration of symptoms.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Previous studies reported that age was associated with poor brain expansion and recurrence of CSDH. 9,11,21,26,29,30 Ro et al reported findings similar to ours, 29 showing that there were more recurrences of CSDH in patients with no brain expansion or brain underexpansion after surgery for CSDH, and that this was associated with age and the duration of symptoms.…”
Section: Discussionsupporting
confidence: 82%
“…A recent study in Korea demonstrated that older patients (≥ 75 years) and patients with recurrent CSDH tended to have poorer mRS grades at 3 months. 29 Previous studies demonstrated that an age threshold of 75 years was associated with unfavorable functional outcomes. 3,19 Consequently, we hypothesized that patients with CSDH with previous brain atrophy have a higher recurrence rate, which is associated with poor brain reexpansion; this might result in less favorable clinical outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…9,39,41 On an institutional level, practices vary from performing no routine CT scan and only clinical monitoring of neurological symptoms to performing as many as 4 routine scans in the first 3 months after surgery. 22,29,30,40,43 Surveys carried out in the United Kingdom, Ireland, and France indicate that between one-third and two-thirds of surgeons order routine scans. 27,33 Systematic scanning of all CSDH patients has been recommended by one study, since certain radiological findings, such as the persistence of midline shift, have been found to predict hematoma recurrence.…”
mentioning
confidence: 99%
“…Fukuhara et al5) reported that brain surface elasticity is an important factor in CSDH. Ro et al14) reported correlation of old age and poor outcome due to brain expansion. In our study, age was not significantly correlated with outcome at discharge and the final follow-up.…”
Section: Discussionmentioning
confidence: 99%